Ensuring reservoir safety into the future proceedings of the 15th conference of the British Dam Society at the University of Warwick from 10-13 September 2008 - Hewlett, Henry (Thomas Telford, 2008)
'Ensuring Reservoir Safety into the Future' discusses key topics and correct events including the state of the UK reservoir management and legislation, and reservoir safety following severe weather in recent years. This book will provide invaluable information on best practice.